PENGEMBANGAN MEDIA KOMIK BERBASIS LITERASI SAINS PADA MATERI GAYA KELAS IV TEMA KEBERAGAMAN DINEGERIKU SUB TEMA KEBERAGAMAN SUKU BANGSA DAN AGAMA DINEGERIKU - Anggun Winata; Ayu Yunike Putri (Universitas Muhammadiyah Gresik, 2020)
This study aims to improve the feasibility of science literacy-based media in students of various styles of material. The results of the PISA and TIMSS survey in this year stated that the scientific literacy skills of Indonesian students are in the low category. One of the efforts that can improve scientific literacy skills is through learning media. Learning media can be in the form of audio, visual, and audiovisual, for grade IV students, visual media can be easily understood by students during learning. The media that will be chosen in this research is comic media based on science literacy. This research uses a development research type. The development of learning media based on scientific literacy is carried out by research and development steps from the Thiagarajan and Semmel models which consist of four steps, namely: defining, planning, developing, and disseminating which will later be used as the research foundation. The development of Upin & Ipin's comic media is based on seven indicators of scientific literacy. This literacy-based comic media was tested with five validators, namely content validation, language validation, graphic validation, scientific literacy validation, and user validation. The results of the validation test stated that 80% of the validation of content experts, 81.25% of language validation, 87.5% of graphic validation, 92.86% of validation of scientific literacy experts, and 95% of user validation. Based on the results of the validation, the content expert validation showed that comic media was included in the feasible category, while for the other four validations it indicated that comic media was included in the very feasible category. Based on the data, it can be concluded that this literacy-based comic media is very feasible in increasing students' scientific literacy skills, especially at the elementary school level.